Pluralism and world order theoretical perspectives and policy challenges - Zhang, Feng (Palgrave Macmillan, 2023)
This volume explores the implications of pluralism for international order. Distinguished contributors from around the world offer insights into the character of a pluralistic world order. They focus especially on the manifestations of international pluralism in great power relations, multilateralism, and regionalism. Contributors examine the myriad challenges a pluralistic world order will face in the years ahead, yet they eschew alarmist conclusions. There is still scope for the great powers to better manage their relations, and equally important, much space for multilateralism and regionalism to play their increasingly important roles in stabilizing world order. Distinctive in bringing the themes of pluralism and world order together in both theoretical exposition and policy discussion, this book offers a stimulating reading for scholars and practitioners of world politics. Feng Zhang is Professor of International Relations and Executive Dean of the Institute of Public Policy at the South China University of Technology in Guangzhou, and editor of the series in which this book appears. He studies Sino-American relations, Chinese foreign policy in East Asia, international relations in East Asian history, and international relations theory. He is the author of Chinese Hegemony: Grand Strategy and International Institutions in East Asian History (Stanford, 2015) and, with Professor Richard Ned Lebow, of Taming Sino-American Rivalry (Oxford, 2020) and Justice and International Order: East and West (Oxford, 2022)
Keywords: Großmachtpolitik; Weltordnung; Multilateralismus; International relations; Great powers; Pluralism / Political aspects; Aufsatzsammlung